On the issues of chronology and periodisation of the Armenian Middle Bronze Age archaeological cultures - Avetisyan, Pavel (ARAMAZD: Armenian Journal of Near Eastern Studies, 2017)
Archaeological periodisation and chronological scales currently applicable for Armenia and the principles of their development were brought into circulation in the 1990s while the assemblages of material culture unearthed since then as well as regularly published extensive results of radiocarbon datings or new stratigraphic data bring forth a demand of additional analysis of the scales and exact specification of their timeframes. It also seems that there is a need of discussing the matters relating to the concepts and methodology of periodisation systems. Specifically, there is a commonly accepted opinion that the Armenian archaeological complexes attributed to Bronze-Iron Ages (with their cultural layers, dwelling and burial structures, typological composition of the inventory, etc.) may be grouped into 8 megacomplexes forming original cultural environments, which in their turn are thought to be archaeological cultures (Early Bronze – ‘Shengavit’ or ‘Kura-Araxes’ culture; Middle Bronze – ‘Early Kurgan’, ‘Trialeti-Vanadzor’, ‘Sevan-Artsakh’, Karmirberd, Karmirvank or Van-Urmia ceramic traditions, Late Bronze-Iron Age – Lchashen-Metsamor and beginning with the 9th century – Urartian or Van-Tosp cultures).